Exacerbations of severe asthma in patients treated with mepolizumab. Issue 6 (13th December 2018) - Shrimanker, Rahul; Pavord, Ian D.; Yancey, Steve; Heaney, Liam G.; Green, Ruth H.; Bradding, Peter; Hargadon, Beverley; Brightling, Chris E.; Wardlaw, Andrew J.; Haldar, Pranabashis
Mepolizumab, a humanised monoclonal antibody that neutralises interleukin-5, reduces exacerbations of severe eosinophilic asthma and chronic obstructive pulmonary disease (COPD) [1, 2]. The beneficial effect of treatment is most obvious in patients with a raised peripheral blood eosinophil count, a group who are at high risk of exacerbation off treatment [2, 3]. Even in this population, exacerbation rates whilst receiving mepolizumab are around one per patient per year. The nature of these remaining exacerbations has not been described. We carried out a post hoc comparison of exacerbations occurring during treatment with mepolizumab or placebo in a previously reported, double-blind, placebo-controlled trial of mepolizumab in severe eosinophilic asthma [1]. We tested the hypothesis that exacerbations in each group differ with respect to change in symptom scores, forced expiratory volume in 1 s (FEV1 ) and inflammatory profile. Exacerbations on mepolizumab are associated with a lower sputum eosinophil level appear less severe in terms of symptoms compared to placebo. These findings raise the possibility that an alternative treatment approach may be needed for these events. http://ow.ly/SoFX30md6of